Doctrin Business Judgment Rule Analysis as an Effort to Protect the Law of Directors of Limited Liability Companies in Indonesia and the United States - Berry Gunawan; Ariawan Gunadi (PT Publikasiku Academic Solution, 2023)
The provisions and implementation of BJR in Indonesia and the United States need to be studied because the latest Company Laws of both countries have codified the principles of BJR generated by court practice so far where BJR elements are regulated imitatively in the Company Law and accompanied by an explanation of the concept of the core elements of BJR. The formulation of the problems in writing this journal are 1) How are the regulations governing the application of the business judgment rule in Indonesia and the United States? 2) how is the application of the business judgment rule principle as a legal protection effort against directors in Indonesia and the United States? The research method used in this journal is normative juridical research with qualitative data analysis. The results showed that 1) regulations governing the application of the business judgment rule in Indonesia are regulated in Law Number 40 of 2007 concerning limited liability companies and OJK Regulation Number 33 / PJOK.04 / 2014 related to BJR which provides protection for directors and commissioners in carrying out their duties are sufficient. Meanwhile, regulations governing the application of the business judgment rule in the United States are regulated in the MBCA 2016. 2) The application of the business judgment rule principle as an effort to protect the law against directors in Indonesia can be applied to protect directors from legal liability as long as there are no elements of fraud, conflict of interest, unlawful acts and intentional misconduct as in the case of Decision Number 121 K/Pid.Sus/2020. Meanwhile, the application of the business judgment rule principle as an effort to protect the law against directors in the United States in accordance with the scope of the directors' responsibilities as in the Disney dispute case, Delaware Supreme Court.